Measuring Saving Rates in New Zealand: An Update - Emma Gorman; Grant M Scobie; Yongjoon Paek (New Zealand Government, The Treasury, 2013)
This paper reviews the flow approach (income less consumption) to measuring saving and the associated trends in sectoral saving rates for New Zealand, as derived from the national accounts. It also presents estimates for the household sector, of the stock measure of savings (changes in net wealth). The latter estimates are found to be consistently greater than the flow measures of household savings. Finally a series of adjustments are made to the flow measures of household and national saving rates. These include adjustment to the boundary between consumption and investment, the impact of inflation and the role of the New Zealand Superannuation Fund. As a result the adjusted measure of net national saving is found, on average to be some 10 percentage points of GDP higher than the raw measure. The associated estimate of the level of adjusted net foreign liabilities is on average 2 percent of GDP lower than the raw data. bilateral exchange rate movements.
Keywords: E21; 330; Savings; measurement; New Zealand; Sparen; Privater Haushalt; Messung; Neuseeland